1995
DOI: 10.2307/3236402
|View full text |Cite
|
Sign up to set email alerts
|

Natural disturbance and tree species coexistence in an old‐growth beech ‐ dwarf bamboo forest, southwestern Japan

Abstract: Abstract. The structure and composition of a cool‐temperate old‐growth beech (Fagus crenata) ‐ dwarf bamboo (Sasa spp.) forest, partially affected by landslide disturbance, in the Daisen Forest Reserve of southwestern Japan, were investigated in relation to forest floor and canopy conditions. All stems ≥ 4 cm DBH were mapped on a 4‐ha plot and analyses were made of population structure, spatial distribution and spatial association of major tree species. The dominant species, F. crenata, which had the maximum D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(103 citation statements)
references
References 41 publications
1
99
0
3
Order By: Relevance
“…Variation in the density of forest understories across sites is important for the maintenance of tree diversity as they can compete with the seedlings of trees [25,65,67] and could lead to ambiguous evidence for the importance of canopy gaps in maintaining tree diversity [5,23]. [2], in their study on changes in species richness and abundance with experimental disturbance in old field plant communities, observed that the impact of disturbance on species richness depends largely on the nature of the dominance and rates of successional or seasonal change of the community.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in the density of forest understories across sites is important for the maintenance of tree diversity as they can compete with the seedlings of trees [25,65,67] and could lead to ambiguous evidence for the importance of canopy gaps in maintaining tree diversity [5,23]. [2], in their study on changes in species richness and abundance with experimental disturbance in old field plant communities, observed that the impact of disturbance on species richness depends largely on the nature of the dominance and rates of successional or seasonal change of the community.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial association between saplings, recruits and canopy trees was analyzed by using Iwao's ω index (Iwao, 1977), which has often been used to analyze the spatial association between two populations (Kohyama et al, 1994;Yamamoto et al, 1995;Manabe and Yamamoto, 1997;Takahashi et al, 2001). This index is calculated by the following equations:…”
Section: Data Analysis 321 Spatial Distributionmentioning
confidence: 99%
“…Forest structure and dynamics of this type of forest ecosystem have often been examined in relation to disturbance regime (Ishikawa and Ito, 1989;Osawa, 1992). For example, several researchers have shown discontinuous age and size distributions and discussed the importance of major disturbances for species coexistence (Oliver and Stephens, 1977;Ishikawa and Ito, 1989;Yamamoto et al, 1995;Abrams and Orwig, 1996;Sano, 1997). Return times for major disturbances are unpredictable, and sometimes exceed more than a millennium (Lorimer, 1977;Canham and Loucks, 1984;Whitney, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Chusquea foliosa) resulta imprescindible, ya que bajo condiciones de poca intervención del bosque se ha encontrado que esta planta puede desplazar a numerosas especies locales (p. ej. Yamamoto et al, 1995).…”
Section: Discusion Riqueza Florísticaunclassified